The effects of explicit instruction of formulaic language on EFL argumentative writing quality - Akkoç, Armağan Bakili; Qin, Jingjing; Karabacak, Erkan (Indonesian Journal of Applied Linguistics, 2018)
This study investigated the effects of explicit teaching of formulaic language on the overall quality of Turkish EFL university students’ argumentative writing. Forty-four freshmen and twenty-seven sophomores participated in the study, with half of them assigned to the experimental group and the other to the control group. Forty target formulaic language items were explicitly taught to the experimental group with a variety of activities for four hours in two weeks. The experimental group was found to increase the overall quality scores of their writing significantly after the intervention. They also outperformed the control group in the immediate post-test although a decrease was observed in the delayed post-test. Moreover, a significantly positive correlation was observed between the frequency of the formulaic language items used and the overall quality scores of the essays. It seemed that the explicit instruction of the target items raised the students’ awareness of formulaic language and improved the overall quality of their writing.